Single quantum dot tracking reveals the impact of nanoparticle surface on intracellular state - Mohammad U. Zahid (Nature Portfolio, 2018)
Quantum dots (QDs) mimic delivery agents for drugs and analytic compounds, but which route do they take inside cells? Here, the authors developed a technique to follow QDs, and they show that zwitterionic nanoparticle surface coatings make for the best delivery vehicle.